Associations between muscular strength and vertical jumping performance in adolescent male football players - França, Cíntia (2023)
This study aimed to investigate the associations between muscular strength tests and vertical jumping performance (countermovement jump [CMJ] and squat jump [SJ]) in adolescent male football players, while controlling for important predictors such as chronological age and body composition. Methods. The sample involved 161 male footballers (mean age: 15.8 ± 1.7 years) from the under-19, under-17, and under-15 age groups. Body fat percentage (BF%) was calculated with Slaughter equations. Muscular strength assessment included handgrip strength and push-up and sit-up tests. Vertical jumping was examined through CMJ and SJ. Pearson correlations and hierarchical regression analyses were run to analyse the data. Results. All muscular strength tests showed significant correlations with CMJ and SJ. Handgrip strength was the most substantial predictor for CMJ (r = 0.43, p < 0.01) and SJ (r = 0.44, p < 0.01). However, regression models identified sit-ups (CMJ: = 0.15, p < 0.01, R2 = 0.23; SJ: = 0.16, p < 0.01, R2 = 0.27) and push-ups (CMJ: = 0.13, p < 0.01; SJ: = 0.15, p < 0.01) as significant predictors after controlling for chronological age, body mass, and BF%. In contrast, BF% remained a significant predictor of jumping performance (CMJ: = –0.43, p < 0.01, R2 = –0.39; SJ: = –0.52, p < 0.01, R2 = –0.52) in the whole hierarchical regression model. Conclusions. This study reinforces the importance of players’ overall physical development, including healthy diet habits, to enhance jumping performance.